Sources and migration pathways of methane and light hydrocarbons in the subsurface of the Southern Po River Basin (Northern Italy). (January 2023) - Ricci, Andrea; Cremonini, Stefano; Severi, Paolo; Tassi, Franco; Vaselli, Orlando; Rizzo, Andrea Luca; Caracausi, Antonio; Grassa, Fausto; Fiebig, Jens; Capaccioni, Bruno
Abstract: This paper presents new chemical and isotopic data on gases from deep oil and gas fields, bubbling gases, dissolved gases in groundwaters and dry seeps of the Southern Po River Basin (Emilia-Romagna, Italy), aiming to (i) characterize and differentiate the various types of deep natural gases; (ii) identify the source(s) of methane and light hydrocarbons in shallow aquifers and surface gas-rich emissions; (iii) propose a conceptual model of natural fluid migration pathways in the sedimentary prism of the Southern Po River Basin. Based on the isotopic composition of CH4 and C2 –C4 n-alkanes, CH4 /(C2 H6 +C3 H8 ) ratio, relative proportion of the C7 hydrocarbons and relative concentration of cyclic compounds with respect to the total cyclic abundance, three main deep reservoirs of hydrocarbons are identified in the subsurface of the Southern Po River Basin: (1) microbial gas hosted in Pliocene-Pleistocene marine sediments, (2) thermogenic gas hosted in Miocene deposits and (3) thermogenic gas produced in Triassic carbonates. Helium isotopes of these deep fluids indicate an almost pure crustal origin (Rc/Ra values = 0.014–0.04), with negligible contributions from mantle-derived helium. A variable contribution of atmosphere-derived fluids is highlighted by low 4 He/ 20 Ne (down to 5.42) and 40 Ar/ 36 Ar (≤319.5) values. Comparison of chemical and isotopic signatures of deep and surficial hydrocarbon occurrences suggests that methane in shallow groundwaters or gas seeps is sourced by microbial gas migrating upward from deep Plio-Pleistocene reservoirs, with no detectable contributions of Triassic or Miocene thermogenic hydrocarbons. At shallow depths (roughly around 20–50 m.b.g.l.), Plio-Pleistocene microbial methane appears to be mainly stored in anoxic aquifers. However, where CH4 further migrates upwards and reaches aerobic environments (e.g., aquifers or soils), it readily undergoes a process of exothermic microbial oxidation mediated by methanotrophic bacteria. Where the structural architecture of the sedimentary sequence favors the migration of fluids, the methanotrophic biofilter is bypassed and CH4 is discharged through soil diffuse degassing or gas bubbling at water wells. We argue that microbial consumption might be able to bio-sequester significant amounts of Plio-Pleistocene deep-sourced methane in the form of CO2 and biomass. Such process might be widespread in the subsurface of the Southern Po River Basin and, possibly, in other foreland basins worldwide. Highlights: New geochemical data of deep and shallow fluids of the Southern Po River Basin. Three main types of deep, crustal-like and CH4 -rich natural gases are distinguished. Shallow CH4 occurrences are fed by Plio-Pleistocene biogenic gases. In shallow aquifers and aerated soils, CH4 undergoes exothermic microbial oxidation. Preliminary conceptual model of fluid sources and migration pathways is proposed.